The ROLE OF PARENTS AGAINTS CHILDREN IN DARING LEARNING THE PANDEMIC COVID 19 AT SD YPK IV PNIEL KLADEMAK SORONG - Krisye Natalia Sedubun; Vantri P. Kelelufna (PEDAGOGIKA: Jurnal Pedagogik dan Dinamika Pendidikan, 2022)
Since the Covid 19 pandemic, it has had an impact on all aspects without exception. One of them is in the field of education. So the government must find a solution so that education can still be done. One of them is distance learning or online learning. Learning which was initially carried out face-to-face at school, but with this pandemic, learning is carried out at home by utilizing existing technology. So that in practice, parents have a role and are responsible for their children's education. The purpose of this study is to get a comprehensive picture of the role of parents in online learning and to find out the implementation of online learning for students at SD YPK IV PNIEL Sorong City. descriptive qualitative. Qualitative research. The research subjects used were parents of 15 PNIEL YPK IV Elementary School students. In this study, the authors used a questionnaire data collection technique (questionnaire) and accompanied by documentation. In this case, the researcher carried out 3 stages of activities in the technical data analysis, namely: data reduction, data display, and conclusion drawing/verification. Based on the index score of each statement, it can be seen that the average obtained is 3.48. online during the covid 19 pandemic at SD YPK IV Peniel Klademak was well based on a score of 3.48